DEVELOPING STUDENT INFORMATION LITERACY SKILL IN SENIOR HIGH SCHOOL - Muhamad Iskhak; Nora Saiva Jannana; Sara Diana; Nur Azizah; Ita Nurmalasari (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2021)
Filtering the abundance of information is done by providing information literacy skills. Information literacy skills need to be possessed by every student at school age to manage information as needed. The school library is one of the facilities that can equip students' information literacy skills. The school library seeks programs and activities related to information literacy. This study examines the efforts made by the library to develop information literacy skills. This research is descriptive with a qualitative approach. The research was conducted at the Ganesha Library of SMA Negeri 1 Jetis Bantul Yogyakarta. Research informants are the head of the library, deputy head of the library, librarians, teachers of reading interest, and students. The data collection techniques are used by observation, documentation, and in-depth interviews. Data were analyzed by data reduction, display data, and conclusion—the validity of the data used by triangulation of sources. The results showed that (1) Students at SMA Negeri 1 Jetis Bantul Yogyakarta had information literacy skills developed with the support of the Ganesha Library. (2) The efforts made by the Ganesha Library to develop students' information literacy skills are through library programs and activities, the role of librarians, the role of teachers, and the empowerment of human resources. The literacy skills possessed by students help them sort out information according to their needs, especially for the development of their academic activities.